2023
DOI: 10.24996/ijs.2023.64.3.38
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Pattern at 500 hPa Geopotential Heights and Its Association with Heavy Rainfall over Iraq

Abstract: Rainfall in the mid-latitudes is highly related to the synoptic pattern at the upper-levels, this study focuses on the relationship between 500 hPa geopotential height patterns and the cyclone at the surface. Synoptic studies that there is a correlation between cyclone at the surface and deepening of the trough at the upper in the mid-latitudes. The results show that when the upper trough is situated over the eastern Mediterranean, this will enhance the advection of warm and moist air from the tropical region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Increased surface water evaporation promotes water shortages, highlighting the need for sustainable solutions to reduce and adjust to these consequences. According to studies conducted in Iraq and around the world by researchers [76,77], climate variations are a significant factor in the growth of sand and dust storms and other extreme weather events, which the regions in Iraq suffered from during recent periods. For the precipitation, the study revealed that the annual precipitation increase over the observed period is variable across periods and scenarios (RCP4.5 and RCP8.5), ranging from + 6.09 to + 14.31% and + 11.25 to + 20.97%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Increased surface water evaporation promotes water shortages, highlighting the need for sustainable solutions to reduce and adjust to these consequences. According to studies conducted in Iraq and around the world by researchers [76,77], climate variations are a significant factor in the growth of sand and dust storms and other extreme weather events, which the regions in Iraq suffered from during recent periods. For the precipitation, the study revealed that the annual precipitation increase over the observed period is variable across periods and scenarios (RCP4.5 and RCP8.5), ranging from + 6.09 to + 14.31% and + 11.25 to + 20.97%, respectively.…”
Section: Discussionmentioning
confidence: 99%